Epigenetic regulation of microglial phosphatidylinositol 3‐kinase pathway involved in long‐term potentiation and synaptic plasticity in rats. Issue 3 (8th November 2019) - Saw, Genevieve; Krishna, Kumar; Gupta, Neelima; Soong, Tuck Wah; Mallilankaraman, Karthik; Sajikumar, Sreedharan; Dheen, S. Thameem
Abstract: Microglia are the main form of immune defense in the central nervous system. Microglia express phosphatidylinositol 3‐kinase (PI3K), which has been shown to play a significant role in synaptic plasticity in neurons and inflammation via microglia. This study shows that microglial PI3K is regulated epigenetically through histone modifications and posttranslationally through sumoylation and is involved in long‐term potentiation (LTP) by modulating the expression of brain‐derived neurotrophic factor (BDNF), which has been shown to be involved in neuronal synaptic plasticity. Sodium butyrate, a histone deacetylase inhibitor, upregulates PI3K expression, the phosphorylation of its downstream effectors, AKT and cAMP response element‐binding protein (CREB), and the expression of BDNF in microglia, suggesting that BDNF secretion is regulated in microglia via epigenetic regulation of PI3K. Further, knockdown of SUMO1 in BV2 microglia results in a decrease in the expression of PI3K, the phosphorylation of AKT and CREB, as well as the expression of BDNF. These results suggest that microglial PI3K is epigenetically regulated by histone modifications and posttranslationally modified by sumoylation, leading to altered expression of BDNF. Whole‐cell voltage‐clamp showed the involvement of microglia in neuronal LTP, as selective ablation or disruption of microglia with clodronate in rat hippocampal slices abolished LTP. However, LTP was rescued when the same hippocampal slices were treated with active PI3K or BDNF, indicating that microglial PI3K/AKT signaling contributes to LTP and synaptic plasticity. Understanding the mechanisms by which microglial PI3K influences synapses provides insights into the ways it can modulate synaptic transmission and plasticity in learning and memory. Main points: Microglial PI3K and its downstream targets are epigenetically regulated by histone modifications and post‐translationally by sumoylation. Microglial BDNF downstream of PI3K modulates neuronal LTP and synaptic plasticity and therefore learning and memory.